More effective solutions? Senior managers and non‐routine problem solving - Decreton, Benoit; Tippmann, Esther; Nell, Phillip C.; Parker, Andrew (Strategic Management Journal, 2023)
Abstract Research Summary Solving non‐routine problems—problems for which current organizational, recurrent action patterns do not offer a predetermined, effective solution—can be an important source of value creation. When these problems occur in subsidiaries of multinational corporations, senior headquarters managers can potentially help solve them. However, whether their involvement is beneficial rests upon the assumptions that they know which knowledge is appropriate and that their involvement does not negatively influence the problem solving process. We challenge these assumptions and theorize that the involvement of senior headquarters managers is negatively related to solution effectiveness, unless senior subsidiary managers are also involved, and especially if problems have an external locus (i.e., primarily relate to the firm's products and services). Our robust results are consistent with our theory. Managerial Summary Companies are often faced with new problems, which represent an opportunity for organizational improvements. But how different types of senior managers influence problem solving effectiveness has remained unclear. Studying problems occurring in foreign subsidiaries of multinational corporations, we find that the involvement of senior headquarters managers is negatively related to problem solving effectiveness. Two reasons explain this result: senior headquarters managers often lack necessary understanding of their subsidiaries' contexts; and their involvement diminishes active participation of subsidiary employees. The negative relationship is especially strong when problems relate to products and services (as opposed to internal processes). Furthermore, we find that senior subsidiary managers can mitigate the negative consequences related to senior headquarters managers' involvement.